The synovial fluid fibroblast-like synoviocyte: A long-neglected piece in the puzzle of rheumatoid arthritis pathogenesis - Dorra Elhaj Mahmoud; Dorra Elhaj Mahmoud; Wajih Kaabachi; Nadia Sassi; Lamjed Tarhouni; Sonia Rekik; Samia Jemmali; Hela Sehli; Maryam Kallel-Sellami; Elhem Cheour; Lilia Laadhar (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a systemic autoimmune disease during which fibroblast-like synoviocytes (FLS) contribute to both joint inflammation and destruction. FLS represent the core component of the synovial membrane. Following inflammation of this membrane, an effusion of cell-rich synovial fluid (SF) fills the joint cavity. Unlikely, SF has been shown to contain fibroblasts with some shared phenotypic traits with the synovial membrane FLS. These cells are called SF-FLS and their origin is still unclear. They are either brought into the synovium via migration through blood vessels, or they could originate within the synovium and exist in projections of the synovial membrane. SF-FLS function and phenotype are poorly documented compared to recently well-characterized synovial membrane FLS subsets. Furthermore, no study has yet reported a SF-FLS single-cell profiling analysis. This review will discuss the origin and cellular characteristics of SF-FLS in patients with RA. In addition, recent advances on the involvement of SF-FLS in the pathogenesis of RA will be summarized. Current knowledge on possible relationships between SF-FLS and other types of fibroblasts, including synovial membrane FLS, circulating fibrocytes, and pre- inflammatory mesenchymal (PRIME) cells will also be addressed. Finally, recent therapeutic strategies employed to specifically target SF-FLS in RA will be discussed.